What the future holds for women after menopause: where we have been, where we are, and where we want to go. (December 2014) - Lobo, R. A.
Abstract With an increasing world population of postmenopausal women, providers of health care need to focus on improving the quality of life as well as the longevity of women. This review emphasizes the importance of health care for postmenopausal women, particularly the role of menopausal hormonal therapy (MHT), from the perspective of where we have been, where we are now, and where we can expect to be in the future. Use of MHT increased dramatically in the 1980s and then fell very abruptly in the early 2000s with the publications of various randomized hormonal trials, including the Women's Health Initiative (WHI). The recent publications from the WHI with 13 years of follow-up are different from the initial reports and do not show an increase in cardiovascular risk in any age group (with the exception of venous thrombosis). Breast cancer risk increased marginally with estrogen/progestogen therapy, related to duration of use, but with estrogen-alone therapy, breast cancer risk decreased significantly, as did mortality. For younger women receiving estrogen alone, there is great consistency between all randomized trials, including the WHI and observational data showing a coronary benefit and a decrease in all-cause mortality. Recent data also confirm the 'timing hypothesis', suggesting that younger women benefit from MHT, while older women do not exhibit this effect. In the future, we will have many more genetic and molecular tools to guide therapy and risk assessment, as we move into an era of personalized medicine. An important opportunity presents at the onset of menopause to prevent diseases which usually occur some 10 years later. Part of this preventative strategy may involve MHT.